Jenis dan Skop Tugas Guru Kanan Mata Pelajaran - Muniandi, Jaya Silar (1998)
The purpose of this study was to obtain an insight into the nature and scope of duties performed by GKMP in secondary schools in West Coast of Sabah. Specifically the study aimed to investigate: (1) the exact nature and range of the duties performed frequently by GKMP; (2) the time / effort devoted to the five main categories of duties (teaching, administration, curriculum, co-curriculum and informal counseling) by GKMP; (3) the problems encountered by GKMP; and (4) the existence of discernible differences in duties performed by GKMP based on factors such as type of school, administrative climate of school, leadership behavior of GKMP, and years of experience as GKMP. Forty three GKMP responded to the survey questionnaire - the method employed to collect the data for the study. Frequency distribution and percentage were obtained and presented in the form of tables. T-test and Chi-Square analyses were employed to test the significance of the associations. The findings indicate that majority of the GKMP in PBS are young and inexperienced teachers. Teaching emerged as the most important responsibility area. They devoted more than thirty percent of their time in the school to teaching. Besides teaching the GKMP also performed curriculum, administrative, co-curriculum and informal counseling duties. It was found that the GKMP, in addition to frequently performing a wide range of curriculum and administrative duties, devoted less than forty percent of their time in accomplishing these duties. The GKMP, on the other hand, did not only devote less time to the co-curriculum and informal counseling duties, but they performed very few duties frequently in these areas. In addition, they did indicate that they would like to devote more time to professional and informal counseling duties. Problems GKMP stated they encountered in discharging their duties, included problems of teachers’ cooperation, lack of competence to accomplish their duties, and personal frustrations due to lack of recognition. The study recommends that further research be conducted in the areas of training facilities, and other factors influencing the nature and scope of duties for GPMK in secondary schools.